2021
DOI: 10.1111/ejss.13163
|View full text |Cite
|
Sign up to set email alerts
|

Aridity and geochemical drivers of soil micronutrient and contaminant availability in European drylands

Abstract: Dryland soils provide different societal and environmental services, such as food supply and biodiversity support. In Europe, most of the dryland areas are devoted to agriculture. In the next decades, both European and worldwide drylands are expected to suffer with increased intensity due to the expected climate change‐derived rise in aridity. Many studies have focussed on aridity‐induced changes in major nutrients in drylands, but little is known of the impact of environmental and biogeochemical factors on mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 79 publications
(93 reference statements)
0
2
0
Order By: Relevance
“…Soil micronutrient deficiency is also widespread in dryland regions of Europe. In a survey study conducted in six European countries, Portugal, Spain, Italy, Hungary, Greece, and Malta, Moreno-Jiménez et al (2021) showed that 60% and 28% of the investigated soils contained lower than adequate levels of Fe and Zn, respectively. Given that an important fraction of crop production takes place in dryland regions, improving the Fe and Zn nutritional status of crop plants growing in these regions is of great importance.…”
Section: Improving Plant Micronutrient Status For Yield and Sustainab...mentioning
confidence: 99%
“…Soil micronutrient deficiency is also widespread in dryland regions of Europe. In a survey study conducted in six European countries, Portugal, Spain, Italy, Hungary, Greece, and Malta, Moreno-Jiménez et al (2021) showed that 60% and 28% of the investigated soils contained lower than adequate levels of Fe and Zn, respectively. Given that an important fraction of crop production takes place in dryland regions, improving the Fe and Zn nutritional status of crop plants growing in these regions is of great importance.…”
Section: Improving Plant Micronutrient Status For Yield and Sustainab...mentioning
confidence: 99%
“…Therefore, drought reduces recovery capacity, soil fertility; the feedback loop exacerbates global warming, potential water pollution, and widespread disruption of biogeochemical cycles. Other micronutrients are also impacted by increasing aridity, for example, reducing the amount of available Fe, Zn, Mo, and Pb and exponentially decreasing the Fe:Zn ratio (Moreno‐Jiménez et al., 2019, 2022).…”
Section: Changes In Carbon and Nutrient Storage In Plant Soil System ...mentioning
confidence: 99%